Relevansi prinsip prudential banking dalam sistem manajemen risiko bank syariah - Pardi, Fira Meilinda (Maliki Interdisciplinary Journal, 2025)
The application of prudential banking principles in the banking industry aims to create a stable and sustainable financial system. In the context of Islamic banking, this principle presents a particular challenge as it must be integrated with the Islamic values that underlie every banking activity. This study aims to analyze the relevance of prudential banking principles to the risk management system in Islamic banking. The findings show a strong alignment between prudential principles and Islamic banking practices, especially in terms of risk management, good governance, and customer fund protection. However, the structural differences in contracts and operational foundations pose challenges in its implementation. Therefore, a regulatory approach is needed to support integration without compromising sharia principles. The roles of the Financial Services Authority (OJK), Bank Indonesia (BI), and the Sharia Supervisory Board (DPS) are crucial in balancing compliance with prudential regulations and Islamic legal requirements.